1990
DOI: 10.1073/pnas.87.4.1259
|View full text |Cite
|
Sign up to set email alerts
|

Erythrocyte metallothionein as an index of zinc status in humans.

Abstract: Metallothionein concentrations in erythrocyte lysates derived from human subjects were measured by an ELISA procedure. IgG obtained from serum of sheep injected with human metallothionein 1 was used in this competitive assay. Subjects were fed a semipurified zinc-deficient diet (0.7 mg of zinc per kg of diet) for an 8-day depletion period after 3 days of acclimation. Fasting plasma zinc concentrations were reduced -7%. Metallothionein in the erythrocyte lysates was significantly decreased to 59% of the initial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1

Year Published

1992
1992
2006
2006

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(68 citation statements)
references
References 23 publications
2
65
1
Order By: Relevance
“…Specificity is poor; levels are also affected by Fe deficiency, diurnal rhythm, and acute infection. Metallothionein is said to be much less responsive to stress and infection in erythrocytes than in plasma (Grider et al 1990), and hence may provide a useful index of Zn status.…”
Section: R O S a L I N D S G I B S O Nmentioning
confidence: 99%
“…Specificity is poor; levels are also affected by Fe deficiency, diurnal rhythm, and acute infection. Metallothionein is said to be much less responsive to stress and infection in erythrocytes than in plasma (Grider et al 1990), and hence may provide a useful index of Zn status.…”
Section: R O S a L I N D S G I B S O Nmentioning
confidence: 99%
“…Early studies by Bremner and associates (Sato et al 1984;Bremner et al 1987) showed that metallothionein could be detected in plasma and erythrocytes of rats, that the levels responded as predicted to changes in Zn status, and that endotoxin treatment increased plasma but not erythrocyte metallothionein content. Cousins and associates (Grider et al 1990;Thomas et al 1992) subsequently reported that erythrocyte levels of metallothionein were increased and decreased in adult men in response to Zn supplementation and deprivation respectively. More recently, this group has developed a sensitive method using the competitive reverse transcriptase-polymerase chain reaction to quantify the level of metallothionein mRNA in human monocytes.…”
Section: New Potential Biomarkers For Assessing Optimal Zinc Nutriturementioning
confidence: 99%
“…At least 3-4 days are required before an increase in metallothionein is observed. This biomarker of exposure is only useful for recent zinc exposure because the metallothionein levels decreased approximately a week after discontinuation of a 63-week supplementation of zinc (Grider et al 1990). Fourteen days after discontinuation of zinc supplements, metallothionein levels were reduced by 61%.…”
Section: Biomarkers Used To Characterize Effects Caused By Zincmentioning
confidence: 99%
“…Increased erythrocyte metallothionein may be an index of zinc exposure in humans (Grider et al 1990). …”
Section: Biomarkers Used To Characterize Effects Caused By Zincmentioning
confidence: 99%